Post-2015 UN development making change happen? - Browne, Stephen; Weiss, Thomas George (London Routledge, 2014)
"Based on extensive original research that has critically examined the role and functions of the organizations of the UN development system, this book seeks to capture in a single volume a comprehensive review of the UN's performance and prospects for development. The contributors each offer extensive experience and familiarity--as practitioners and researchers--with the UN and development; and the book will contribute to the urgently needed debate on the reform of the UN development system at a critical juncture"--
1 UN roles and principles governing multilateral assistance / Bjorn Skogmo -- Evolution of the UN development system / Craig N. Murphy -- Drivers of change for the UN's future role / Richard O'Brien -- Funding the UN system / Silke Weinlich -- Evaluating the UN development system / Robert Picciotto -- Making the UN more accountable and transparent / Richard Golding -- Aligning UN development efforts and peacebuilding / W. Andy Knight -- The economics of peace : is the UN system up to the challenge? / Graciana del Castillo -- Can peacebuilding drive the UN change agenda? / Michael von der Schulenburg -- The UN and the post-2015 development agenda / David Hulme and Rorden Wilkinson -- "We the Peoples" in the UN development system / Roberto Bissio -- Revisiting UN development : the prospects for reform / Cécile Molinier and Stephen Browne -- Conclusion : Post-2015, making change happen? / Stephen Browne and Thomas G. Weiss.
Includes bibliographical references and index.
Keywords: United Nations Development Group; United Nations -- Economic assistance; United Nations -- Technical assistance; Economic development projects; Political Science/ General; Political Science / International Relations / General; Political Science / International Relations / Treaties